Four-word lexical bundles in Chinese-English consecutive interpreting—A comparative study between professionals and trainees - Fang Tang; Fang Tang; Shuzhen Jiang (Frontiers in Psychology, 2022)
As comparative studies on lexical bundles between professional interpreters and trainees are pedagogically significant but rare, this experimental study initiates a comparison on the product and process of four-word lexical bundles in Chinese-English consecutive interpreting between these two groups. Frameworks regarding the structure and strategy of lexical bundles are established to analyze the product of lexical bundles produced by these two groups, and data including interpreters’ interpreting products, notes as well as retrospection and interviews are collected to analyze their process of producing lexical bundles. The results show that the types (Type) and frequencies (Token), except diversity (TTR), of lexical bundles with the “noun and/or prepositional phrase fragments” structure and/or the “equivalence” strategy from professionals are significantly higher than those from trainees. Reasons for inter-group similarities and differences in structural and strategical distributions (product) and strategy adoption (process) are also analyzed. Based on the established interpreting-tailored lexical bundle frameworks, this comparative study presents and explains similarities and differences between professionals and trainees and implies suggestions for the training and learning of interpreting.